(untitled) (Scientia Agropecuaria, 2024)
Tara (Caesalpinia spinosa) is an emblematic legume tree of Peruvian dry forests and is a multi-purpose tree for tannins and gum, in particular. Despite its importance, the microbiological aspects associated with tara are not currently considered in forest management, and its nodulation status remains contentious. This study sought to confirm or deny C. spinosa’s nodulation status and, using P. sativum as a trap plant, to investigate the effects of C. spinosa on rhizospheric rhizobial communities. The study revealed a lack of tara nitrogenase activity and that C. spinosa is a non-nodulating species. Soil samples were collected from a tara plantation to investigate their effect on tara and pea growth, in a tara planting row (R), between 2 rows (IR), and outside the plantation (OP). For the total biomass growth parameter, soil R significantly promoted tara and pea growth. For root length and leaf chlorophyll content, there was a significant difference in favor of C. spinosa grown on R and IR soils compared with OP soil. Fifty-seven pea strains were characterized by analyzing the partial 16S-23S rDNA intergenic spacer. The phylogenetic tree showed high diversity with five clusters of Rhizobium spp. in the R. leguminosarum–etli clade and phylogenetic specificity according to soil origin. This study provides information of interest on the non-nodulating nature of C. spinosa and demonstrates the substantial influence of tara on rhizospheric bacterial communities. The results of this study highlight the need to integrate microbiological factors into forest management strategies to improve the ecological sustainability and agricultural yield of tara plantations.